2012
DOI: 10.1038/eye.2012.62
|View full text |Cite
|
Sign up to set email alerts
|

A nurse-led ocular oncology clinic in Liverpool: results of a 6-month trial

Abstract: Purpose To describe the design and implementation of a nurse-led clinic in a tertiary adult ocular oncology service and to assess its feasibility and patient satisfaction. Methods Patients with a melanocytic uveal tumour attending for review during an initial 6-month trial period were assessed in a dedicated ocular oncology clinic by an ophthalmic nurse practitioner. These were:(1) patients who would have been discharged back to the referring hospital but whose ophthalmologist refused to continue their follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…This study revealed that patients were highly satisfied with their experience of nurse‐led clinics in Queensland, expressing favourable responses to questions about access to services, coordination of care, and satisfaction and safety in a similar way to previous studies into patient satisfaction with nurse‐led clinics in other specialities (Sandinha et al ; Townsend ; Berglund et al ). Ample consultation time, in‐depth specialised knowledge, listening to and understanding individual patient needs and a holistic approach were identified as factors contributing to patients’ satisfaction.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study revealed that patients were highly satisfied with their experience of nurse‐led clinics in Queensland, expressing favourable responses to questions about access to services, coordination of care, and satisfaction and safety in a similar way to previous studies into patient satisfaction with nurse‐led clinics in other specialities (Sandinha et al ; Townsend ; Berglund et al ). Ample consultation time, in‐depth specialised knowledge, listening to and understanding individual patient needs and a holistic approach were identified as factors contributing to patients’ satisfaction.…”
Section: Discussionsupporting
confidence: 82%
“…The efficacy of nurse-led clinics has been evaluated for a variety of medical conditions including diabetes, hypertension and cardiovascular disease (Gabbay et al 2006), showing favourable associations with lifestyle changes and hospital admissions, as well as improvements in quality of life, disease related knowledge, adherence to treatment regimens, and self-management behaviours (Grady et al 2000;Loftus & Weston 2001;Griffiths 2004). Nurse-led clinics have also been associated with high levels of patient satisfaction (Sandinha et al 2012;Townsend 2014;Berglund et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Patients are referred either to an oncology centre with a special interest in uveal melanoma, their local hospital, or the Nurse Ocular Oncology Clinic (NOOC) at the Royal Liverpool University Hospital (RLUH). At RLUH, patients have an MRI scan (without contrast) in the morning and attend the NOOC in the afternoon, when they are informed of the MRI result 14. A health psychologist and an ophthalmologist are on hand.…”
Section: Methodsmentioning
confidence: 99%
“…If such patients do not need to see an ocular oncologist, because the risk of ocular complications is low, they are reviewed at a follow-up clinic run by specialist oncology nurses. 29 Surveys using anonymous questionnaires have shown high levels of satisfaction among patients attending these clinics.…”
Section: Follow-upmentioning
confidence: 99%